Mekanisme Dua Wajah Kekuasaan Terhadap Ideologi 212 - Siti Nurjanah (Jurnal komunikan, 2022)
The two-face mechanism that originated from the 212 Islamic defense action movement in the country. The so-called two faces, namely religion and political parties of government, have the power to defend the country because of blasphemy by political figures. The act of defending Islam was carried out because of the dissemination of a video from a figure of Basuki Tjahaja Purnama (Ahok) by issuing the contents of a verse from the Qur'an surah Al-Maidah 51. He called for any religion other than Islam to be made a leader and that the clerics had been deemed a lie by ahok. The purpose of this study is to analyze and understand how political games are developed on the mechanism of the face of power against ideology 212 especially in the case of the 2019 gubernatorial election party democracy and the 212 Islamic defense action. The method used with descriptive analytical research methods, methods are compiled based on an overview related to the analysis of power within the ideology of political parties and Islamic groups. The result of this study is the mechanism of political parties and Islamic groups against the ideology of 212 which is shaded by clerical figures by providing motivational intake to the public to follow up on the desecration of Qur'anic verses. The mechanism is based on the steps of interpreting by forming a drive from the MUI. If the cleric has given an opinion and decision regarding blasphemy and must be tried, the government must also participate in that opinion. That means the majority of religious groups are still proportional to the political power in the country's governing chamber. As for the ethics of Islamic parties and groups in the ideology of islamic defense action 212 is grown because the country must come out of polemics of misrepresentation, misleading and outside government rules. Ethics is concerned with morals. The goal is to maintain religious unity in Indonesia. In conclusion, because of the emergence of blasphemy, seeds of disillusionment with other religions have emerged accusing each other and justifying what is going on. The latter relates to the role and function of Islamic religious parties and groups towards the 212 Islamic defense action,as we know the blasphemy problem resulted from the dissemination of videos in 2016 and resurfaced in 2019 where the year was in the heat of the governorship election. Many of the parties and religious groups even beyond that played their part so that the dispute became big. The time parameter from the upload of the video to the governor's election is five years, and it shouldn't have reaped polemics. However, because in 2019 a new election was held in Jakarta, a lot of people usedthe object as a political game, and flocked to appreciate the public to join and give a function in speaking out. Keywords: Political Parties, Islamic Groups, Defending Action 212 and Political Power